Des petits nombres à l’amorce d’un scandale sanitaire - Solène Lellinger (Revue d'anthropologie des connaissances)
The process leading up to the withdrawal of Mediator (benfluorex) in 2009 highlights the key role played by an alert launched by a team at Brest University Hospital concerning the drug's adverse effects. Clinicians use different types of evidence, from case reports to studies on hospital databases. This article analyzes the development of a causal link between a drug and its adverse effects. While medical alerts are initially based on small numbers, data from pharmacoepidemiological studies reinforce the demonstration.